Islamic Spiritual Care in Supporting Emotional Stability in High Care Unit Patients: A Systematic Review - Wulandari, Mega; Muhith, Abdul (Journal of Applied Nursing and Health, 2024)
Background: Patients in the High Care Unit (HCU) often experience increased levels of stress, depression, and anxiety, especially those who require long-term care between 3 and 15 days. The psychological pressure that patients face in HCU can affect the quality of recovery and elicit a variety of emotional responses that require attention in the treatment process. The purpose this study aims to analyze the impact of Islamic Spiritual Care (ISC), specifically through the recitation of Murottal Al-Qur'an Surat Ar-Rahman, in supporting emotional stability (stress, depression, and anxiety) in patients in the High Care Unit (HCU). Methods: This research method uses systematic review using the PRISMA technique. Data was obtained from journals contained in PubMed, Science Direct, and Google Scholar from 2020-2024, based on the identification results based on inclusion criteria and feasibility reviews, and fifteen articles were obtained for review. Results: The results of the implementation of Islamic Spiritual Care (ISC) through Murottal Al-Qur'an therapy, especially Surat Ar-Rahman, are effective in supporting the emotional stability of patients in the High Care Unit (HCU). Conclusion: Murottal Al-Qur'an therapy, particularly Surat Ar-Rahman, as a component of Islamic Spiritual Care (ISC), can be utilized as a practical non-pharmacological approach to reduce anxiety, stress, and depression in patients in the High Care Unit (HCU).